Democracy, governance, and law - Deflem, Mathieu (Emerald Publishing Limited, 2025)
Issues related to democratic ideals and realities are very much at the forefront of many public discussions today. These questions move societies in many contexts and with respect to multiple institutions, not least among which are law, government, and the interconnections between them. This volume of Sociology of Crime, Law and Deviance is devoted to the theme of Democracy, Governance, and Law. It brings together scholars to debate sociological, socio-legal, and related insights from the social and behavioral sciences concerned with important contemporary questions on democracy, and its role for matters of governance and law. With each chapter focusing on a specific topic such as abortion, the rule of law, criminal legal systems, electoral politics, white terror, challenges to democracy, and more, the collection is theoretically and methodologically diverse, covering a broad range of issues to address important questions on governance and law, and in relation to the idea and reality of democracy. Democracy, Governance, and Law makes a timely contribution, bringing together authors from various disciplines and specializations.
Keywords: Democracy -- Governmant policy.; Law -- Government -- General.; Political structures: democracy.; Government powers.; elektronické knihy; electronic books